2020
DOI: 10.3390/g12010001
|View full text |Cite
|
Sign up to set email alerts
|

Are People Willing to Tell Pareto White Lies? A Review and New Experimental Evidence

Abstract: We explore whether individuals are averse to telling a Pareto white lie—a lie that benefits both themselves and another. We first review and summarize the existing evidence on Pareto white lies. We find that the evidence is relatively limited and varied in its conclusions. We then present new experimental results obtained using a coin-tossing experiment. Results are provided for both the UK and China. We find evidence of willingness to tell a partial lie (i.e., inflating reports slightly) and high levels of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The evidence that individuals are more willing to tell a Pareto lie than a selfish lie is, however, mixed (Cartwright et al, 2020). This mixed evidence may reflect the subtle relationship between lie aversion and social preferences (Sanchez-Pages and Vorsatz, 2009;Cappelen et al, 2013;Okeke and Godlonton, 2014;Biziouvan Pol et al, 2015;Li et al, 2022).…”
Section: Framework To Evaluate Digital Interaction and Dishonestymentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that individuals are more willing to tell a Pareto lie than a selfish lie is, however, mixed (Cartwright et al, 2020). This mixed evidence may reflect the subtle relationship between lie aversion and social preferences (Sanchez-Pages and Vorsatz, 2009;Cappelen et al, 2013;Okeke and Godlonton, 2014;Biziouvan Pol et al, 2015;Li et al, 2022).…”
Section: Framework To Evaluate Digital Interaction and Dishonestymentioning
confidence: 99%
“…Moreover, we have seen that the effect of communication media may differ for a Pareto and selfish lie. We, therefore, use a simple extension to the standard coin-flipping task that allows us to study dishonesty in a setting with direct payoff inter-dependence (see also Biziou-van Pol et al, 2015;Hermann and Ostermaier, 2018;Thielmann and Hilbig, 2019;Cartwright et al, 2020).…”
Section: The Coin-flipping Taskmentioning
confidence: 99%
“…Adults engage in lying for a variety of reasons, ranging from maximizing self‐benefits to protecting others (Bucciol & Piovesan, 2011; Kaplar & Gordan, 2004). Some lies are even driven by more than one motive (Erat & Gneezy, 2012; Gino et al., 2013), as in Pareto lies that benefit both the lie‐teller and the lie recipient (e.g., a sportsperson may use illegal drugs to improve their own performance as well as to help their team win the competition; Cartwright et al., 2020; Kim & Kim, 2021). The question is, how do we reach this level of complexity in our attempt to conceal the truth?…”
Section: Introductionmentioning
confidence: 99%
“…2 That supervisors could lie about the performances of the agents they supervise is a rather standard assumption in the literature to which this paper relates (from Tirole 1986, to Saygili andKucucksenel 2019). It is true that experiments have shown that lie aversion can be rather strong (see Cartwright et al 2021). Yet, Cartwright et al (2021) also point out that the evidence on lie aversion is yet to be conclusive, yielding very different predictions depending on the type of lie (white, black, altruistic, selfish and so on) and the type of experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…It is true that experiments have shown that lie aversion can be rather strong (see Cartwright et al 2021). Yet, Cartwright et al (2021) also point out that the evidence on lie aversion is yet to be conclusive, yielding very different predictions depending on the type of lie (white, black, altruistic, selfish and so on) and the type of experimental design. In addition, even if almost a half of the experimental subjects surveyed by Cartwright et al (2021) were reluctant to tell even a Pareto white lie (i.e., a lie improving the wellbeing of all the agents involved), the share of individuals having no problem in telling lies range from 80 to 40% depending on the type of the latter.…”
Section: Introductionmentioning
confidence: 99%